Electrical conductivity structure of Aravalli and Tural hot springs (western part of DVP) inferred from magnetotelluric data - Subba Rao, P.B.V.; Deshmukh, Vasu; Vijaya Kumar, P.V.; Singh, A.K. (My University, 2022)
Both audio-magnetotelluric and magnetotelluric data were acquired across Aravalli and Tural hot springs (in Konkan region of Deccan volcanic province). The objective is to bring out the geoelectrical crustal structure beneath these geothermal zones. Two-dimensional inversion of data brings out different conductivity anomalies (i) shallow conductivity anomaly related to upward propagation of meteoric water through faults/fracture zones, (ii) major fracture/fault zones extending up to mid-crustal depths through which Deccan volcanism may have erupted and (iii) the presence of mid-crustal conductivity anomalies are related to trapped carbonate fluids that are linked to thermal effects of Deccan volcanism.
Keywords: Deccan volcanism; Magnetotelluric; Hot springs; Konkan region; Faults/fracture zones; Aravalli and Tural hot springs